2010
DOI: 10.1111/j.1365-2265.2010.03788.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of persistent radioiodine uptake in the neck shown by diagnostic whole body scan in patients with differentiated thyroid carcinoma after initial surgery and remnant ablation

Abstract: Neck US and serum sTg, but not DxWBS, were useful diagnostic tools during follow-up of patients with persistent uptake in the neck at DxWBS. A second ablation was not necessary when neck US showed no evidence of disease, especially in patients with very low sTg concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…A recent study by Kim et al. demonstrating ablation failure is not an independent risk factor for recurrence in patients with persistent radioiodine uptake in the neck on diagnostic I‐131 scanning following initial surgery and I‐131 remnant ablation is also reassuring 20 . In this study, a significant proportion of patients with residual I‐131 uptake on follow‐up diagnostic scanning had spontaneous disappearance of residual I‐131 activity (and normalization of serum Tg levels) on subsequent scanning.…”
Section: Discussionsupporting
confidence: 57%
“…A recent study by Kim et al. demonstrating ablation failure is not an independent risk factor for recurrence in patients with persistent radioiodine uptake in the neck on diagnostic I‐131 scanning following initial surgery and I‐131 remnant ablation is also reassuring 20 . In this study, a significant proportion of patients with residual I‐131 uptake on follow‐up diagnostic scanning had spontaneous disappearance of residual I‐131 activity (and normalization of serum Tg levels) on subsequent scanning.…”
Section: Discussionsupporting
confidence: 57%
“…However, few studies have focused on the patients with negative Tg and positive 131 I -WBS results. Several previous studies have shown that negative Tg and positive 131 I -WBS results could be found in 4.4% -28.6% of the patients [3][4][5][6]. However, consensus on the clinical significances and management strategies has not yet been reached.…”
Section: Introductionmentioning
confidence: 98%